2020
DOI: 10.1039/d0sm00488j
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven computational scheme for the nonlinear mechanical properties of cellular mechanical metamaterials under large deformation

Abstract: Cellular mechanical metamaterials are a special class of materials, whose mechanical properties are primarily determined by their geometry. But capturing the nonlinear mechanical behavior of these materials, especially with complex...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…We observe from the contour plots that the building blocks with five different shapes show similar responses when d > 0. This indicates that under tensile forces, the springs generally have similar mechanical behaviors, which is consistent with our previous work [Xue et al, 2020]. On the contrary, the energy contours show richer responses that are highly nonlinear when d < 0, i.e., under compression.…”
Section: Training Validation and Testsupporting
confidence: 91%
See 1 more Smart Citation
“…We observe from the contour plots that the building blocks with five different shapes show similar responses when d > 0. This indicates that under tensile forces, the springs generally have similar mechanical behaviors, which is consistent with our previous work [Xue et al, 2020]. On the contrary, the energy contours show richer responses that are highly nonlinear when d < 0, i.e., under compression.…”
Section: Training Validation and Testsupporting
confidence: 91%
“…Previous studies have shown that the mechanical properties of CMMs are highly sensitive to the pore shapes [Bertoldi et al, 2010, Overvelde et al, 2012, Overvelde and Bertoldi, 2014, Xue et al, 2020. Under uniaxial compression, mechanical instabilities at the scale of unit-cell often lead to pattern transformations at the structural scale.…”
Section: Quasi-static Loadingmentioning
confidence: 99%
“…These two properties have been shown to be sensitive to the geometric features of the pores. 3,40 Here, we use MSOM to optimize these features for the desired properties under given macroscopic loadings.…”
Section: Optimizing Static Macroscopic Properties Of Cmms Due To Inst...mentioning
confidence: 99%
“…In recent years, many such datadriven constitutive modeling approaches have been presented for anisotropic, hyperelastic, and inelastic material behavior, e.g., using reduced basis models [34,35], clustering techniques such as self-consistent clustering analysis [36][37][38], polynomial or spline interpolation [39][40][41], or machine mearning (ML) with artificial neural networks (ANN) [42][43][44][45][46][47][48][49][50]. To the best of our knowledge, only in [51] ANN-based constitutive models have been applied to the multiscale simulation of highly geometrically nonlinear, buckling-prone microstructures. However, the work is restricted to 2D applications, material symmetry is not considered in the material model formulation, and the accuracy of the effective constitutive model itself is not assessed.…”
Section: Introductionmentioning
confidence: 99%